‘Yoga is Not a Sport’: Mobilisation of Self-Employed Yoga Teachers Against Fitness Platforms - Joanna Bronowicka (Labour & Law Issues)
The Covid-19 pandemic accelerated the rise of fitness platforms offering students access to online classes.  However, there appears to be little research on how fitness professionals perceive and engage with these platforms. This article focuses on a group of yoga teachers in Berlin who resisted the growing influence of fitness platforms in their field. Using a mixed-methods approach, this case study of the Fair Yoga Initiative investigates why and how this group of self-employed workers mobilised against platforms. Previous research suggests that self-employed platform workers face numerous challenges in building collective power, including workforce heterogeneity and fragmentation. This study reveals the importance of subjective interests in overcoming these challenges and motivating yoga teachers to defend their profession from pressures of valorisation represented by fitness platforms. The article explores how gender might play a part in shaping subjective interests in this feminised profession. Moreover, the text highlights the importance of self-employed workers’ rights in the current debates about regulations of digital labour platforms in the European Union. Despite operating in a restrictive legal environment, in this case the yoga teachers leveraged their collective power to influence public discourse on fitness platforms. I argue that new worker organizations can spotlight the rights of specific professional groups and contribute to the development of laws that better protect their interests.